DEKONSTRUKSI LAKON GRAFFITO - AHMAD FAISHAL; MOH. HARIYANTO (Universitas 17 Agustus 1945 Surabaya, 2018)
A text of drama is importance and an integral part of any drama perfomarnces. However, it seems that it has obtained lack of appreciation and has been separated from a performance. It is needed only when it will be performed. This article tries to explore the ideas of deconstruction in Akhudia’s Grafito. Deconstructive method proposed three steps in its reading a text, that is verbal stage, textual, and meaning stages. On the verbal stage, the reading of the text is inteded to uncover the paradox and contradiction critically. On the textual stage, the reading is focused on finding the meaning of the whole text. The meaning stage will trace the linguitic meaning of the text. In Grafito, one can read Akhudiat shows a rebellion and an opposition toward the social construction such as religous institution. The characters are given various characteristics, such as being capable to create setting, properties, being shadows, or inside voices which suggest unconvensional dimention propose a paticular artistic value. Keywords: discourse, deconstruction, Graffito